PERAN DAN KONTRIBUSI ILMU KALIGRAFI PADA MASA DAULAH ABBASIYAH - Fahrurrozi S; Nurhasanah Sibarani; Khuzaiman Putri Alfi Syahrina (Jurnal Shaf, 2024)
Calligraphy is one of the works of art that is very popular in the Islamic world and has even become one of the extracurriculars that is in great demand among Islamic students. Far from this, the art of calligraphy gave a lot of roles and contributions in the Islamic world and developed rapidly during the Abbasid Daula  era. This is what encourages researchers to examine this discussion in a straightforward and thorough manner. The purpose of the researchers to study this discussion is to find out the role and contribution of calligraphy art in the Islamic world. The method used by researchers regarding this discussion is to use a qualitative method, namely the technique of collecting data from literature study through relevant references. The results of this study are that the art of calligraphy plays a very big role and contributes to the Islamic world because it is still strong with the value of monotheism. Keyword: art, calligraphy, abbasid.